(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
Brachiopods obtained from several Triassic localities in North Dobrogea, in Romania, are described. Upper Spathian and Aegean Hallstatt-type red limestones have been sampled in the Deşli Caira section, proposed as the GSSP for the base of the Anisian. The Bithynian brachiopods mostly originate from the Tubiphytes-microbial buildup in the Mahmudia quarry, and also from the Hallstatt-type limestones of Agighiol and Orta Bair. Their age estimates are supported by ammonoids collected from the same beds. The upper Spathian and Aegean assemblages of Deşli Caira consist of four rhynchonellids, with one genus and two species newly described, Ortarhynchia petersi gen. n. sp. n. and Austriellula iordanae sp. n. The Bithynian assemblages comprise the most diverse fauna, with 15 species, four species of which are newly described, Ortarhynchia petersi gen. n. sp. n., Piarorhynchella kittli sp. n., Ptychomentzelia dobrogeana sp. n. and P. simionescui sp. n. In the Tubiphytes facies of Mahmudia, the assemblage is numerically dominated by mentzeliids and dielasmatids, forming 84.8 % of the whole assemblage. Spiriferinids and rhynchonellids form the minor component. Instead, rhynchonellids prevail in the Hallstatt facies at Agighiol and Orta Bair. The assemblages described here are hardly comparable with those of the western Tethys. The Bithynian assemblage is very different from its equivalent described from the substage stratotype in Turkey. In North Dobrogea, the carbonate substrate and clear and agitated water supported an assemblage with high diversity. In contrast, in Bithynia, the brachiopod community dwelled on a softer and muddier substrate, with higher density and lower diversity. The locality of Aghdarband (Iran) also delivered Bithynian brachiopods, forming another different assemblage. The recovery and radiation of brachiopods after the P/T crisis is discussed in the framework of Palaeo-Tethyan palaeogeography, making comparisons with the South China localities.